The identity crisis in public administration revisited some definitional issues and the Philippine setting - Reyes, Danilo R. (Philippine Journal of Public Administration, 1979)
Paramount to settling the identity crisis (or the issue of conceptual identity) being undergone by public administration is the resolution of its definitional boundary - if it could be defined precisely - and a coherent and systematic organization of normative theory. Previous to the description of the crisis, the concentration of studies in American Public Administration had been oriented towards specialized, applied concerns (service type) as against the construction of a general and valid theoretical framework (academic or basic type). The identity crisis, however, may not be a serious problem from the point of view of Philippine Public Administration due to three distinct features: (a) Public Administration has maintained some disciplinary independence from allied disciplines and has not been insecure about its relationships with Political Science; (b) the politics-administration dichotomy has no strong tradition and is thus inapplicable here; (c) the peculiarities of a developing country have necessitated Philippine Public Administration to give emphasis on or favor to service type researches. Thus, the identity crisis in Public Administration becomes relevant and worthwhile only if it is viewed from the perspectives of actual Philippine conditions and development aspirations. Certainty is an illusion, and repose is not the destiny of man.